IMAGE POSITIONING DEVICE, METHOD AND PROGRAM - YOSHIDA KENICHI (2022)
To accurately position a slice image between three-dimensional images with a relatively small calculation amount in an image positioning device, method and program.SOLUTION: A processor acquires a first three-dimensional image formed of at least one slice image and a second three-dimensional image formed of a plurality of slice images, matches at least one of the gravity center of a subject region in the slice image surface and the inclination of an inertia main axis between one comparison source slide image included in the first three-dimensional image and two or more comparison destination slice images of the plurality of slice images included in the second three-dimensional image, derives an evaluation value expressing the similarity between the comparison source slice image and each of the two or more comparison destination slice images after matching at least one of the gravity center of the subject region and the inertia main shaft, and decides a comparison target slice image corresponding to the comparison source slice image among the comparison destination slice images based on the evaluation value.SELECTED DRAWING: Figure 3 【課題】画像位置合わせ装置、方法およびプログラムにおいて、３次元画像間におけるスライス画像の位置合わせを比較的少ない演算量にて精度よく行う。【解決手段】プロセッサは、少なくとも１つのスライス画像からなる第１の３次元画像および複数のスライス画像からなる第２の３次元画像を取得し、第１の３次元画像に含まれる１つの比較元スライス画像と第２の３次元画像に含まれる複数のスライス画像のうちの２以上の比較先スライス画像のそれぞれとの間で、スライス画像面内の被写体領域の重心および慣性主軸の傾きの少なくとも一方を一致させ、被写体領域の重心および慣性主軸の少なくとも一方を一致させた後の、比較元スライス画像と前記２以上の比較先スライス画像のそれぞれとの類似度を表す評価値を導出し、評価値に基づいて比較先スライス画像のうちの比較元スライス画像に対応する比較対象スライス画像を決定する。【選択図】図３